2000
DOI: 10.1063/1.481183
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic coupling in neutral and charged Cr2, Mn2, and CrMn dimers

Abstract: Theoretical ab initio studies of neutral, cationic and anionic Cr 2 , Mn 2 , and CrMn dimers have been carried out to explore the progression of magnetic coupling with the number of electrons. It is shown that while Cr 2 and Cr 2 Ϫ have antiferromagnetically coupled atomic spins, Cr 2 ϩ has a ferromagnetic ground state closely followed by an antiferromagnetic state. On the other hand, all Mn 2 dimers are ferromagnetic, irrespective of the charge. The neutral CrMn is ferrimagnetic while the charged CrMn are ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
57
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 56 publications
7
57
3
1
Order By: Relevance
“…However, Nesbet's prediction was seemingly confirmed by ESR studies of a Mn 2 molecule in low temperature (Ar, Kr, and Xe) matrices [1]. Very recent and extensive first-principles density-functional studies have confirmed, in odds with experimental results, Harris and Jones prediction of a ferromagnetic Mn dimer [8][9][10][11][12][13]. Current opinion is that van der Waals interaction is holding together the manganese dimer.…”
Section: Introductionmentioning
confidence: 79%
“…However, Nesbet's prediction was seemingly confirmed by ESR studies of a Mn 2 molecule in low temperature (Ar, Kr, and Xe) matrices [1]. Very recent and extensive first-principles density-functional studies have confirmed, in odds with experimental results, Harris and Jones prediction of a ferromagnetic Mn dimer [8][9][10][11][12][13]. Current opinion is that van der Waals interaction is holding together the manganese dimer.…”
Section: Introductionmentioning
confidence: 79%
“…The local magnetic moments of the Cr sites also appear ferromagnetic or antiferromagnetic aligment for n≥4. In Cr n B clusters (n=4, 5,6,8,9), the total magnetic moments are enhanced compared to that of corresponding Cr n clusters, respectively. For Cr 7 B clusters, the total magnetic moment is reduced compared to Cr 7 cluster.…”
Section: Magnetic Propertiesmentioning
confidence: 91%
“…Its 3d 5 4s 1 electronic configuration results in strong d-d bonding in dimer with short bond length (1.68 Å) [1−4], while bulk chromium is antiferromagnetic with a body-centered-cubic (bcc) structure (nearest Cr-Cr distance: 2.50 Å) [5]. In last decade, the bonding nature and electronic structure in small chromium clusters have been studied by experimental and theoretical methods [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The geometric and magnetic properties of chromium clusters have been performed by density functional theory (DFT) [20,21].…”
mentioning
confidence: 99%
“…
[24,25] Wirz eigen hier experimentell, dass Cr 2 + in der Tate inen Hochspingrundzustand besitzt und sich damit in der elektronischen Konfiguration deutlich von Cr 2 unterscheidet. Hierbei nutzen wir den Effekt des magnetischen zirkularen Rçntgendichroismus (XMCD) in der L 2,3 (2p!3d)-Rumpfanregung,d essen Vermessung eine Standardmethode zur Bestimmung der Magnetisierung von Festkçrpern oder Dünnschichtsystemen der 3d-Übergangsmetallverbindungen darstellt, von uns hier aber auf freie Cr 2 + -Ionen in einer linearen Tieftemperatur-Quadrupolfalle in einem starken Magnetfeld [26][27][28][29][30][31] angewendet wird.
…”
unclassified